Differences in steep quality and body mass index in asthmatic children and healthy control group - YURDALAN, SAADET UFUK (CODON PUBLICATIONS, 2021)
Introduction: Childhood asthma has become a serious public health problem. Obesity has been determined to be one of the risk factors of asthma. Aim: We aimed to determine the difference in body mass index (BMI) and sleep quality in pediatric asthmatic individuals compared to their peers. Method: Thirty children aged 8-17 years were followed up in the Pediatric Outpatient Clinic for asthma along with 30 healthy children. The BMI percentile values of the children were recorded. The Pittsburgh Sleep Quality Index was used to assess sleep quality. Results: Each group in our study had 10 girls and 20 boys. The mean age was found to be 11.76 +/- 2.69 years in asthma group and 11.33 +/- 2.29 years in the healthy group. The asthma group were found to be more obese than the healthy group (P = 0.033). There was a significant difference between groups interested in a sport (P = 0.028) and steep quality (P = 0.007). Conclusion: It was observed that the asthma group had more obesity and poorer sleep quality than the healthy group. Further, it was determined that in the asthma group, the level of interest in any sport was less than that in the healthy group. We think that high obesity in the asthma group reduces the effect of corticosteroids, and the continuity of nighttime cough symptoms causes deterioration in sleep quality. We conclude that participation in sports activities should be encouraged to reduce the level of obesity in asthmatic children. (C) 2021 Codon Publications. Published by Codon Publications.
Keywords: body mass index; obesity; pediatric asthma; sleep quality; OBESITY; MECHANISMS; SEVERITY; SLEEP